2022
DOI: 10.31557/apjcp.2022.23.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Cancer Screening in Asian Americans: Need for Community Outreach Programs

Abstract: Cancer is the leading cause of death in Asian Americans (AA) (Hastings et al., 2015;Torre et al., 2016; CDC, 2019). AAs are the only racial group in the United States to experience cancer as the number one cause of mortality, accounting for 27% of all deaths (American Cancer Society, 2016). Despite the identification of best practices for early detection through screenings, AAs have one of the lowest rates of preventive cancer screenings of all minority groups in the United States (Chen, 2005;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…Indeed, participants with low educational levels reported significantly poorer knowledge, negative attitudes, and poor practices. These results are in agreement with previous research carried out by Cheung et al [34] and Wu et al [35], who also found that the level of education was a determinant of KAP scores. In addition, the study by Haron et al [20] revealed a significant correlation (p < 0.05) between a higher educational level and good knowledge scores.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, participants with low educational levels reported significantly poorer knowledge, negative attitudes, and poor practices. These results are in agreement with previous research carried out by Cheung et al [34] and Wu et al [35], who also found that the level of education was a determinant of KAP scores. In addition, the study by Haron et al [20] revealed a significant correlation (p < 0.05) between a higher educational level and good knowledge scores.…”
Section: Discussionsupporting
confidence: 93%